2018
DOI: 10.1186/s12868-018-0404-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of serum in a rat heroin self-administration model undergoing reinforcement based on 1H-nuclear magnetic resonance spectra

Abstract: BackgroundUnderstanding the process of relapse to abused drugs and ultimately developing treatments that can reduce the incidence of relapse remains the primary goal for the study of substance dependence. Therefore, exploring the metabolite characteristics during the relapse stage is valuable.MethodsA heroin self-administered rat model was employed, and analysis of the 1H-nuclear magnetic resonance-based metabolomics was performed to investigate the characteristic metabolite profile upon reintroduction to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…The effects of another addictive opioid, i.e. heroin (3,6-diacetylmorphine), were investigated using a heroin self-administration rat model (Ning et al 2018 ). The authors focused their attention on the serum metabolic modifications occurring upon reinforcement (heroin reintroduction) after abstinence.…”
Section: Drug-induced Biological Effects On the Metabolomementioning
confidence: 99%
“…The effects of another addictive opioid, i.e. heroin (3,6-diacetylmorphine), were investigated using a heroin self-administration rat model (Ning et al 2018 ). The authors focused their attention on the serum metabolic modifications occurring upon reinforcement (heroin reintroduction) after abstinence.…”
Section: Drug-induced Biological Effects On the Metabolomementioning
confidence: 99%
“…In the present study, CYP exposure caused a significant elevation in the level of glutamine (P < 0.05) in L-group at 24 h and in H-group at 24 and 96 h. In addition to, a significant increase in the level of glutamate in H-group at both time points ( Fig.2-A, Table.1). Glutamine is the precursor for glutamate synthesis and plays a vital role in removing excess of nitrogen from brain suggesting that CYP allowed excessive accumulation of nitrogen in the brain of carp (Ning et al 2018). The rise in glutamate (P < 0.05), an excitatory neurotransmitter, in brain tissue was previously reported in the brain of goldfish exposed to lambda-cyhalothrin (Li et al 2014).…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…In the current study, higher concentration of CYP (1 μg/L) increased the level of tyrosine (P < 0.05) at 96 h (Fig.2-B). In the liver, tyrosine is synthetized from phenylalanine and then converted into L-3, 4-dihydroxyphenylalanine (L-DOPA) in brain tissue (Ning et al 2018). A previous study in young rat reported that prenatal exposure to fenvalerate resulted in disruption in dopaminergic receptors (Malaviya et al 1993).…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…However, it was found that no single analytical platform is capable of capturing all metabolomics information in a single run (Dinis-Oliveira, 2014). LC- and GC-MS, nuclear magnetic resonance (NMR) spectroscopy, and LC with electrochemical detection are all used (Ning et al, 2018), but the most widespread analytical instruments utilized are MS and NMR spectroscopy. The advantages and disadvantages of MS or NMR use within the field of metabolomics have been extensively discussed in corresponding reviews (Schlotterbeck et al, 2006; Pan and Raftery, 2007).…”
Section: Metabolomicsmentioning
confidence: 99%
“…From a pharmacological point of view this is not surprising. As stated e.g., by Ning et al neuronal activity is extremely energy demanding, and the brain energy supply requires oxidative metabolism of glucose in mitochondria and demands lactic acid from glycolytic processes (Ning et al, 2018). However, albeit e.g., MA and GHB act at different pharmacological targets both were shown to influence succinate concentrations (Zheng et al, 2014; Palomino-Schatzlein et al, 2017).…”
Section: Applications Of Metabolomics For Forensic (Toxicology) Purposesmentioning
confidence: 99%